2008
DOI: 10.1111/j.1600-0536.2008.01468.x
|View full text |Cite
|
Sign up to set email alerts
|

Contact sensitization to metals in Taiwan

Abstract: Several patient factors were characterized related to metal sensitization in the Taiwanese population. The sources of exposure were further discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
23
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 24 publications
9
23
1
Order By: Relevance
“…Compared with previous studies, the percentage of people allergic to nickel has increased in our center over the last 10 years (from 17%) [24], despite the “nickel directive” – in force since 2005. An increase in allergies to nickel has recently been observed in the United States and other countries where there are no regulations limiting exposure to the metal [25, 26]. Allergy to nickel is observed significantly more often among women (visible in our patients), which is explained by early exposure to allergens contained in jewelry, especially earrings.…”
Section: Discussionmentioning
confidence: 68%
“…Compared with previous studies, the percentage of people allergic to nickel has increased in our center over the last 10 years (from 17%) [24], despite the “nickel directive” – in force since 2005. An increase in allergies to nickel has recently been observed in the United States and other countries where there are no regulations limiting exposure to the metal [25, 26]. Allergy to nickel is observed significantly more often among women (visible in our patients), which is explained by early exposure to allergens contained in jewelry, especially earrings.…”
Section: Discussionmentioning
confidence: 68%
“…In addition, nickel is one of the causes of allergic contact dermatitis . The prevalence of nickel‐sensitized individuals ranges from 10% to 24% . Due to its design, our study could not confirm a causal relation between endometriosis and nickel allergy; however, hypothetically, a nickel allergy could be an antecedent event to the onset of endometriosis.…”
Section: Discussionmentioning
confidence: 99%
“…In dermatitis patients, the prevalence is higher (adults, 12%‐25%; children, 5%‐30%) . Nickel allergy has been less investigated outside of Europe, although persistently high prevalences have been observed in Asia and North America . A higher prevalence of nickel allergy in individuals with atopic dermatitis has been shown in some studies, whereas others have found negative associations .…”
Section: Epidemiology Of Nickel Allergymentioning
confidence: 99%